Antigenic drift in type A influenza virus: Peptide mapping and antigenic analysis of A/PR/8/34 (HON1) variants selected with monoclonal antibodies - Laver, W. G. (1979)
Variants of A/PR/8/34 (HON1) influenza virus, having hemagglutinin molecules with probably a single altered antigenic determinant, were isolated by growing the virus in the presence of the monoclonal hybridoma antibody PEG-1. The variants were analyzed by peptide mapping and characterized antigenically by using PEG-1 and four other monoclonal hybridoma antibodies to PR8 hemagglutinin. Peptide maps of the large hemagglutinin polypeptide, HA1, from 8 out of 10 variants showed a single changed peptide. This peptide from two of the variants was analyzed, and in each case a serine residue in the wild-type hemagglutinin was replaced by leucine in the variant. Although these eight variants showed identical peptide maps, one could be discriminated antigenically from the others with one of the hybridomas. (The peptide maps represented about one-third of the HA1 molecule.) Of the other two variants, one gave the same HA1 map as the wild type, but could be distinguished antigenically from wild-type virus by two of the hybridomas. The other was unique, and could be distinguished, both antigenically and by peptide mapping, from the other variants. Since a large number of the variants selected with PEG-1 showed the same peptide change, it is likely that this alteration in amino acid sequence (serine to leucine) was responsible for the inability of the variants to bind PEG-1 monoclonal antibody. We do not know, however, whether the changed amino acids were located within the antigenic sites or whether the change occurred somewhere else in the hemagglutinin molecule and altered the determinants through conformational changes.